E-SATISFACTION AND E-LOYALTY: THE ROLE OF BRAND IMAGE AND E-SERVICE QUALITY - Satria Tirtayasa; Jufrizen Jufrizen; Wimpi Siski Pirari; Maya Sari Maya Sari (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2024)
The effect of brand image and e-service quality on e-loyalty is mediated via e-satisfaction, as this study's empirical evidence demonstrates. Four variables are used in the study model, which applies the idea of mediation. SEM-PLS is used to assess each association. A total of 384 Medan-based Shopee e-commerce users who have made at least three online purchases were included in this study using a purposive sample technique. An online questionnaire was used for data collecting, and the partial least squares (PLS) analysis method was used for data analysis. The study's findings revealed that e-satisfaction was positively and significantly impacted by brand image, e-satisfaction was positively and significantly impacted by e-service quality, e-loyalty was positively and significantly impacted by brand image, e-satisfaction positively and significantly impacted by e-loyalty, and brand image affects e-loyalty through e-satisfaction and e-service quality through e-satisfaction. According to this research, e-satisfaction acts as a mediator between brand image and e-service quality's effects on e-loyalty and e-commerce. The e-satisfaction measure should be analyzed or used as an independent variable rather than a mediating variable, according to recommendations for additional research.